MEDIATING ROLE OF MOBILE BANKING BETWEEN SERVICE QUALITY AND ADAPTIVE PERFORMANCE OF MANAGERS IN SMES - HUSSAIN, ABID; BILAL, MUHAMMAD; SHABBIR, SARA (Bulletin of Business and Economics (BBE), 2021)
This study looks into the mediating role of mobile banking between service quality and managers’ adaptive performance in Pakistan’s small and medium-sized businesses. The purpose of this research is to discover how service quality and mobile banking affect managers’ adaptive performance at work. The study’s target population consists of managers or owners of SMEs listed in Chambers of Commerce in Pakistan’s capital cities. As part of the more detailed investigation, 422 replies were obtained, representing a 50% response rate. SEM measurement and structural models were created to test the hypotheses. The results demonstrate that partial mediation is evident in the case of service quality and adaptable performance as direct beta without mediation is significant and positive, as well as in the presence of a mediator (mobile banking) service quality and adaptive performance are significant and positive. The outcomes of this study will assist academia, SMEDA, app developers, the banking sector, and practitioners in understanding the importance of service quality and mobile banking usage. Future researchers should do an empirical study evaluating the effects of information quality, system quality, and mobile device use on managers’ adaptive performance in SMEs and major firms in Pakistan.